(untitled) (Conferencea, 2024)
The article describes the creation of religious-scientific theory of Sufism by Imam al-Ghazali and Ibn al-Arabi and the division of these theories into moderate and philosophical ones, Ghazali’s place in Islamic rationalism, Ibn al-Arabi’s ideas of religious tolerance and pluralism and their importance today.